THE EFFECT OF CONSUMER CONFIDENCE ON WORD OF MOUTH IN MAYBELLINE PRODUCTS - Choiriyah, Faizzatul; Rejeki, Asri; Endah, Noer Suci (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This study aims to determine the effect of consumer trust on word of mouth on Maybelline products. This study uses a quantitative approach using incidental sampling technique and gets 59 samples of students from the Accounting Study Program and Management Study Program. The method of collecting data on the Consumer Trust and Word of Mouth variables used a questionnaire compiled and modified by the researcher on a Likert scale. Test the validity of the scale using content validity. Scale reliability test using Alpha Cronbach technique. The results of data analysis using the Simple Linear Regression technique with the statistical program IBM SPSS Statistics 25, it is known that the value of R Square or the coefficient of determination is 0.403 from the consumer confidence variable, which means that the influence of consumer confidence on word of mouth is 16,3%, while the rest is influenced by other variables. The results of the regression coefficient test show that in the Sig column the independent variables and constants have a significance level below 0.05 and this shows that there is an influence of consumer trust on word of mouth.